IMPLEMENTATION OF POLICIES TO STRENGTHEN MILITARY SATELLITES AS AN EFFORT IN SUPPORTING THE SEA DEFENSE STRATEGY AND UPHOLDING STATE SOVEREIGNTY - Ananda Meci Hadyanti; Lukman Yudho Prakoso; Aries Sudiarso (Bajang Institute, 2023)
Defense Policy is a basis for realizing the Strategic Plan of a State Special Military Satellite which is a state defense and security need for implementation and regulation so that it can run ideally. The Ministry of Defense as one of the leading sectors in realizing the existence of military satellites in Indonesia, so that it can accommodate all needs for military satellites that can be used in ways that can be implemented easily, simply and as efficiently as possible. So that the research objective is to provide an in-depth analysis of the implementation of policies regarding military satellites issued by the ministry of defense. So that it becomes an important thing to do an evaluation so that it can find solutions and strategies in implementing the implementation of these policies. The research method is using a qualitative method with data collection in the form of interviews, indirect observation and literature studies, which are then processed with Edward III's Policy Implementation theory and strategy theory for how to maximize efforts to implement policies on military satellites. The results of the research are in the Policy Implementation Process, in this case namely the Military Satellite Policy contained in the General Policy on National Defense issued by the Ministry of Defense, there are communications that have not been implemented to Policy Executors such as Bakamla and TNI AL, while to make strategies for implementing these policies, with the concept of means, ways and ends, provides output of the concept of implementation strategy resulting from a comparison of Chinese and American military satellite policies, which have important criteria, namely leadership style factors, budget base and supporting infrastructure.